Distribution patterns of bats in Eastern Mediterranean region through a climate change perspective - Keşişoğlu, Ari. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2010., 2010)
The impact of climate change on different species has been analyzed multiple times in various geographies. The main aim of this study was to determine how climate change will affect 18 different bats species in the eastern Mediterranean region. Using presence only modelling techniques and relevant bioclimatic data forecasts according to two different climate change scenarios (A2A and B2A) of Intergovernmental Panel on Climate Change (IPCC), the potential geographic distribution of bat species in the eastern Mediterranean region for current period and the years 2020, 2050 and 2080 was modelled. The results suggest that climate change will affect bats negatively throughout the 21st century in the studied area on two fronts: i) species richness will deteriorate, and ii) the total area occupied by bats will decline. These impacts will be more severely observed in Turkey’s coastal areas, northwest Turkey, Red Sea coasts, Israel, and west of Syria and Jordan. Using only bioclimatic variables as factors and thus not using any land cover (or habitat) data was the main limitation of the study. Hence the models and results of the study present "best case" scenarios.
Keywords: Climatic changes.; Bats -- Climatic factors.